Právní zastoupení územně samosprávného celku v občanském soudním řízení - Scholzová, Renata; Fiala, Josef, 1953-; Masarykova univerzita. Právnická fakulta (2013)
Práce reaguje na změny, které nastaly v rozhodovací praxi Ústavního soudu v posledních dvou letech v oblasti náhrady nákladů právního zastoupení v občanském soudním řízení, pokud advokát zastupuje územně samosprávný celek. Práce obsahuje přehlednou prezentaci změn přijatých soudy v dané oblasti a rozbor nejvýznamnějších argumentů Ústavního soudu pro jeho závěr, že právní zastoupení je v případě územně samosprávných celků neúčelně vynaloženým nákladem a že si mají územně samosprávné celky zajišťovat hájení svých zájmů u civilních soudů vlastními prostředky.
The work responds to the changes that have occurred in the decision practice of the Constitutional Court in the last two years. It focuses on significant departure from existing case-law issued by the Constitutional Court concerning the obligation to pay the court costs to territorial self-governing units (local governments, municipalities), if they are represented by legal representatives (attorneys). Author refers to specifics of activities of territorial self-governing units, which relate to their right as legal persons to own property and carry out the associated rights and obligations of the owner. Author draws attention to the fact that especially larger cities have a number of claims. These claims arise from individuals or legal entities (debtors) as a result of their bad economic situation or as a result of lack of their responsibility event. as a result of small respect to their legal obligations. This work describes that for territorial self-governing units was in the case of such debt and still is possible only in exceptional cases waive recovery (forgive the debt). Therefore, the territorial self-governing units become the plaintiff in a civil proceeding for the enforcement of financial performance and in cases of eviction. The same scheme also applies to situations where the territorial self-governing unit is listed on the defendant. This is usually the case when the territorial self-governing units recovered a third party claims for damages, exceptionally claims for unjust enrichment, there are also cases declaratory relief. The work presents and discusses the most important arguments of the Constitutional Court and describes the consequences of the new practice for the budgets of territorial self-governing unit.
Dizertace (MPA)--Masarykova univerzita, Právnická fakulta, 2013
Vedoucí práce: Josef Fiala
Anglické resumé
Keywords: občanské soudní řízení; územní samospráva; civil procedure; regional administration; závěrečné práce; final theses